Cortical interneuron specification: the juncture of genes, time and geometry. (February 2017) - Bandler, Rachel C; Mayer, Christian; Fishell, Gord
Graphical abstract: Highlights: The GEs produce many types of GABAergic projection neurons and a majority of GABAergic interneurons. Spatial origin, birthdate, and mode of division influence interneuron fate. Subdomains exist within each GE, producing different neuronal subtypes over time. PV and SST-expressing interneurons can originate from the same progenitor. Different modes of divisions are biased for producing different interneuron subtypes. Abstract : A fundamental question in developmental neuroscience is how hundreds of diverse cell types are generated to form specialized brain regions. The ganglionic eminences (GEs) are embryonic brain structures located in the ventral telencephalon that produce many inhibitory GABA (γ-Aminobutyric acid)-ergic cell types, including long-range projection neurons and local interneurons (INs), which disperse widely throughout the brain. While much has been discovered about the origin and wiring of these cells, a major question remains: how do neurons originating in the GEs become specified during development as one differentiated subtype versus another? This review will cover recent work that has advanced our knowledge of the mechanisms governing cortical interneuron subtype specification, particularly progenitors' spatial origin, birthdates, lineage, and mode of division.